EFFICIENCY OF TOOTH DISCOLORATION TREATMENT USING BLEACHING SYSTEMS WITH DIFFERENT TYPES OF ACTIVATION AND CONCENTRATION OF HYDROGEN PEROXIDE - Nikolishyna, E.V.; Marchenko, A.V.; Nikolishyn, I.A. (World of Medicine and Biology, 2018)
The results of tooth discoloration treatment with the use of bleaching systems containing various concentrations of hydrogen peroxide and different types of activation are highlighted. The possibilities of modern aesthetic dentistry make it possible to conduct the bleaching procedure highly efficient and safely. However, up to date, disputes about the safety of this treatment, the development of possible complications and the expediency of this procedure in general have not ceased among dentists. According to the literature data, about 67% of patients suffer from various types of hyperesthesia during the individual stages and after bleaching procedure. There are the following reasons of the dental hyperesthesia development: exposure time of the bleaching agents, frequency of applications, solution pH, congenital hypersensitivity of the human teeth, patient’s age, gender etc. A number of authors associate the emergence of hyperesthesia after in-office bleaching with the use of lamps, which produce a large amount of heat. In view of the above, the dentist has to know fully and work out the right approach to the bleaching technique, its contra-indications, advantages of different agents and techniques, and therefore prevent possible complications. 27 patients with an average degree of tooth staining (C2, A3, D3, B3, A 3.5) were selected for the clinical study including TER-test, the Green-Vermillion hygiene index, the PMA index and the index of tooth hyperesthesia intensity (ITHI). Analysis of outpatient charts had shown that the stable forms of dye staining (color C2, A3, D3, B3, A 3.5) prevailed in the structure of discolorations. It was found that acquired forms of discolorations dominated in their structure in 22 of 27 patients. Congenital staining was found in 5 patients with an average degree of color predominating. The analysis of the obtained results showed that professional bleaching of discolorations of teeth with using bleaching systems containing different concentration of hydrogen peroxide and different type of activation is effective in 100%. The activation type of a whitening gel does not affect the result significantly. However, in the course of the study a higher percentage of cases of hyperesthesia was found in 76.9% patients from the group where chemically activated 38% gel was used, compared to 64.3% patients, who a light-activated 35% gel was applied for.